A comparison of variations in blocking mechanisms of membrane-fouling models for estimating flux during water treatment. (November 2020) - Khan, Imtiaz Afzal; Lee, Yong-Soo; Kim, Jong-Oh
Abstract: This study investigates five different fouling models and contributing factors in membrane-filtration blocking mechanisms in a constant-pressure mode. A polyvinylidene fluoride membrane was used to study the fouling effects of a complex mixture of foulants (a latex-bed suspension, soybean oil, and inorganics) on pristine and chemically cleaned membranes in the presence of humic acid. A significance ratio in linear regression results (p-value) was used to assess the contribution of fouling mechanism in each model. The results indicate that Hermia and Bowen's models correspond closely with the experiment results and confirms that complete blocking is dominant fouling model. We also verify that each developed model is dependent on its experimental conditions. Moreover, the role of complex mixtures, including inorganic foulants, in the fouling process needs to be modified as modified for ceramic membranes and natural organic matter removal in the Wiesner and Kilduff models, respectively. Graphical abstract: Image 1 Highlights: Evaluation of change in membrane fouling behavior after chemical cleaning. Variation of existing fouling models for complex fouling mixture. Introduce participation equation for better representation of fouling. Statistical confirmation of Hermia's model for fouling representation.